Measuring and Removing Dissolved Metals from Stormwater in Highly Urbanized Areas - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 767: Measuring and Removing Dissolved Metals from Stormwater in Highly Urbanized Areas presents prototype best management practices (BMPs) for the removal of dissolved metals in stormwater runoff.The report presents three conceptual configurations in detail: two vault system configurations for urban and rural settings, and an inlet scupper with media for bridge deck drainage systems.The report also includes standard protocols to accurately measure the levels of dissolved metals in stormwater. Practical guidance on the use of these protocols is provided in an appendix to the final report. The report is accompanied by an Excel spreadsheet on CD designed to assist in sizing the filter bed in the vaults and the bridge deck inlet scupper.The CD is also available for download from TRB2019s website as an ISO image. Links to the ISO image and instructions for burning a CD from an ISO image are provided below.Help on Burning an .ISO CD ImageDownload the .ISO CD ImageCD Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively \

Prospects for Managed Underground Storage of Recoverable Water - National Research Council (The National Academies Press, 2008)
Growing demands for water in many parts of the nation are fueling the search for new approaches to sustainable water management, including how best to store water. Society has historically relied on dams and reservoirs, but problems such as high evaporation rates and a lack of suitable land for dam construction are driving interest in the prospect of storing water underground. Managed underground storage should be considered a valuable tool in a water manager's portfolio, although it poses its own unique challenges that need to be addressed through research and regulatory measures.

Desalination: A National Perspective - National Research Council (The National Academies Press, 2008)
There has been an exponential increase in desalination capacity both globally and nationally since 1960, fueled in part by growing concern for local water scarcity and made possible to a great extent by a major federal investment for desalination research and development. Traditional sources of supply are increasingly expensive, unavailable, or controversial, but desalination technology offers the potential to substantially reduce water scarcity by converting the almost inexhaustible supply of seawater and the apparently vast quantities of brackish groundwater into new sources of freshwater. Desalination assesses the state of the art in relevant desalination technologies, and factors such as cost and implementation challenges. It also describes reasonable long-term goals for advancing desalination technology, posits recommendations for action and research, estimates the funding necessary to support the proposed research agenda, and identifies appropriate roles for governmental and nongovernmental entities.

Review of the EPA's Economic Analysis of Final Water Quality Standards for Nutrients for Lakes and Flowing Waters in Florida - National Research Council
The Environmental Protection Agency's estimate of the costs associated with implementing numeric nutrient criteria in Florida's waterways was significantly lower than many stakeholders expected. This discrepancy was due, in part, to the fact that the Environmental Protection Agency's analysis considered only the incremental cost of reducing nutrients in waters it considered \

Urban Stormwater Management in the United States - National Research Council (The National Academies Press, 2009)
The rapid conversion of land to urban and suburban areas has profoundly altered how water flows during and following storm events, putting higher volumes of water and more pollutants into the nation's rivers, lakes, and estuaries. These changes have degraded water quality and habitat in virtually every urban stream system. The Clean Water Act regulatory framework for addressing sewage and industrial wastes is not well suited to the more difficult problem of stormwater discharges. This book calls for an entirely new permitting structure that would put authority and accountability for stormwater discharges at the municipal level. A number of additional actions, such as conserving natural areas, reducing hard surface cover (e.g., roads and parking lots), and retrofitting urban areas with features that hold and treat stormwater, are recommended.